Tourist Accommodation Choice and Destination Development: The Case of Vanuatu - Addison, Anna (Auckland University of Technology, 2020)
The accommodation choice made by visitors has a key role to play in tourism development, helping to shape visitors’ impressions of the destination and their resultant impacts. Accommodation facilities are essential prerequisites for hosting tourists and can also facilitate and stimulate tourism growth in regions looking to bolster visitor numbers and tourism’s economic impact. Investment in tourism accommodation also represents one of the largest areas of foreign and domestic investment in many developing nations. There is limited literature addressing the role that accommodation choices play in destination development and this is particularly the case in the developing island nations of the South Pacific. This thesis focuses on the characteristics of visitors associated with different types of accommodation in Vanuatu. The accommodation sector in the nation is undergoing considerable development, and important decisions are being made about the type of accommodation that will underpin tourism development in the future. The thesis reviews the current accommodation structure in Vanuatu and provides a detailed insight into the visitor characteristics associated with accommodation choice. The thesis adds an important new dimension to understanding tourism development in Vanuatu. It also develops visitor profiles associated with different accommodation types and these will be of value to communities, business and government as they engage in planning future tourism development. The data upon which the thesis is based are drawn from the Vanuatu International Visitor Survey (IVS) (2015–17). The thesis reviews demographics and visitor spend and behavioural characteristics of visitors with a largely quantitative and descriptive analysis of the data. The research then delves into the qualitative dimensions of the Vanuatu IVS, exploring, particularly, aspects of visitor satisfaction. NVivo software was used to conduct the review of the qualitative data. Visitor profiles are developed and presented based on the Vanuatu Department of Tourism’s accommodation classifications. Resorts, including Boutique accommodation, were the most popular accommodation choice for holidaymakers. The average spend for those staying in Resorts was US$195 per person per day and the Boutique visitor had the highest expenditure across all types at $291 per person per day. The Guest House and Island Bungalow group visited the outer islands significantly more than any other groups, and had an average daily spend of US$164 per person. Those staying in Hotels (comprising both regular and corporate hotels) were predominantly visiting for business and conference purposes and spent, on average, US$232 per person per day. The Motels group includes self-contained accommodation; this group’s average length of stay was 8.9 days, with an average daily spend per person of US$168.00. The Multi-type group is a combination experience reflected in the other groups, and these visitors had an average daily spend of US$188.00 per person. Insights into the characteristics of visitors associated with different types of accommodation can inform development decisions such as which locations and accommodation types to invest in. This research provides Vanuatu’s tourism industry and the Vanuatu Government with insights into the effects that existing and future accommodation development can have on visitor profiles and broader development outcomes. The research provides an important baseline for future comparative work. The ability to review IVS data over time will direct governments and investors how to best cater for evolving visitor demand and meet community needs.
Keywords: Accommodation; Choice; Tourism; Development; Vanuatu; Visitor; Profile